Colorectal cancer in Crohn’s disease: a series of 6 cases - Ishimaru, Kazuhide (Surg Case Rep, 2021)
BACKGROUND: Colorectal cancer (CRC) is the most malignant complication in patients with Crohn’s disease (CD). We report 6 cases of CD-related CRC treated surgically at our hospital. CASE PRESENTATION: From 2010 to 2016, six CD patients were diagnosed with CRC. All patients were diagnosed with CD at < 25 years old, and the interval from onset of CD to diagnosis of CRC was > 10 years (range, 15–42 years) in all patients. The histological type of cancer was mucinous carcinoma in two cases, well-differentiated tubular adenocarcinoma in two cases, and moderately differentiated tubular adenocarcinoma in two cases. CRC was detected by screening colonoscopy in three cases (50%), and from clinical symptoms in the remaining three cases (50%). Two cases underwent colonoscopy within 2 months after symptom onset, detecting CRC in the relatively early stage. However, one case was diagnosed with advanced-stage CRC by endoscopy 1 year after symptom onset, and experienced poor prognosis. CONCLUSIONS: Regular surveillance colonoscopy is needed to detect early-stage CRC in CD patients. Clear surveillance methods need to be established based on evidence.